Validitas Pengembangan Bahan Ajar IPA Sekolah Dasar Berbasis Teori Belajar Bruner - Ratin Wahyu Juni Atma; Mijahamudin Alwi; Dina Fadilah (LP2M STIT Palapa Nusantara, 2023)
The need for creative, innovative, effective, and fun learning development to make students more active in learning activities, requires teachers to continue to provide learning innovations, especially in science subjects. Thus, the purpose of developing elementary school science teaching materials based on Bruner's learning theory is to find out whether the developed teaching materials are suitable for use in the learning process. This study uses the development of Dick and Carey. Determination of the validator by purposive sampling technique, and data collection techniques using a validator assessment sheet, while the data analysis technique uses quantitative to qualitative descriptive. The results showed that from material experts to the model book the actual score was 54 and was in the range of scores of 44,19 < X 54,58 with a good category, in the teacher's book the actual score was 54 and it was in the range of scores of 44,19 < X 54,58 in the good category, and the student's book with an actual score of 58 and in the range of scores of 47,59 < X 58,79 with a good category. The results of the display expert on the model book, the actual score is 19 and is in the range of scores 16,99 < X 20,99 with good category, the teacher's book is the actual score is 54 and is in the range of scores 44,19 < X 54,58 and the actual score of the student book is 42 and is in the range of scores of 37,39 < X 46,19. While the validation results from practitioners are on average 88 and in the range of scores of X > 79,78 with a very good category. The results of this study indicate that the product is suitable for use in the learning process.